COMPRESSION PHYSIC-CHEMICAL PROPERTIES OF MILK FROM CAMEL, COW, GOAT, HUMANE AND SHEEP IN AL-MUTHANNA GOVERNMENT, IRAQ - Eabaid, Frhan ala Allah; Gatea, Eqbal A.; Hamdan, Israa Abd Alhasan (International Journal of Psychosocial Rehabilitation, 2020)
Milk is very important nutrients, that human cannot be dispensed with, in this study eight parameters of physic-chemical properties besides energy that obtained from the species that study (camel, cow, goat, sheep, and human milk) and compared between milk species. The milk samples were collected in Al- Muthanna province during the period from July- October 2018, the samples that are collected analyzed by EKO- Milk Scanner. Results that obtained from analysis input to statically analyzed by using ANOVA (version 10.spss), at significant differences at P<0.05, and there were significant differences between types of milk. The parameters under study were higher in sheep’s milk than other species which tested, except on lactose was higher in human milk.